American Knees - Wong, Shawn, 1949- (Book collections on Project MUSE., 2005)
The loves of Raymond Ding, a Chinese-American who wonders if one can be a lapsed Chinese "like a lapsed Catholic." He becomes the first divorced person in his family, but eventually finds true love with a half-Japanese, half-Irish girl from the Midwest who cures him of his ethnic angst.